The marine catfishes of the genus Bagre (Siluriformes; Ariidae) from the Western Atlantic - Marceniuk, Alexandre P.; Oliveira, Claudio [UNESP]; Sales, João Bráullio L.; Betancur-R, Ricardo (Springer Nature, 2022)
The marine catfishes of the family Ariidae present an ample range of life histories. Although most species are demersal, and are common in estuaries and coastal zones, species of the genus Bagre Cloquet, 1816, are pelagic and are typical of coastal and offshore environments. While the genus Bagre is a well-defined monophyletic group, the taxonomy of its species is complex, and the four recognized species include a total of 12 synonyms. Based on morphological and molecular data, we provide a redescription of Bagre marinus Mitchill, 1815, restricting its geographic range to the Gulf of Mexico and the southeastern coast of the USA. We also resurrect Bagre filamentosus Swainson, 1839 (formerly a junior synonym of B. marinus), a species endemic to the Caribbean Sea and the Atlantic coast of South America. Finally, we redescribe Bagre bagre Linnaeus, 1766, clarifying geographic range of all species. Our study contributes to the alpha taxonomy of the genus Bagre and to biogeographic and evolutionary history of its species in the western Atlantic.
Keywords: Bagre filamentosus; Biodiversity; Biogeography; Integrative taxonomy; Molecular markers